Efektivitas Pemberdayaan Keluarga terhadap Perkembangan Sensorik, Motorik, Visual Persepsi dan Kemandirian Aktivitas Anak Berkebutuhan Khusus - prasaja, prasaja; Harumi, Linda; Saloka, Erayanti (Profesi (Profesional Islam) : Media Publikasi Penelitian, 2025)
Children with special needs according to the Ministry of State Minister for Empowerment (Asiva Noor Rachmayani, 2015) are children with limitations or extraordinary, in terms of physical, mental-intellectual, social, or emotional, which have a major influence on the growth and development process compared to other children of the same age. This study aims to determine the effect of family empowerment programs on the development of sensory, motoric, visual perception and independence on activities of daily living (ADL) of children with special needs. This study used a pre-experimental research design with a one group pre and post test design to see changes in developmental maturity, and independence on activities of daily living before and after receiving intervention. Data analysis in this study was the paired Samples t-test. The results of this study showed the effect of providing family empowerment programs on sensory development (p = 0.000), motoric (p = 0.000), visual perception (p = 0.000), and independence of AKS (p = 0.000). So it can be concluded that the family empowerment program (providing training and monitored home programs) has proven effective in increasing the development of sensory, motor, visual perception and independence on ADL in children with special needs